Modifiers of radiation effects in the eye. (November 2017) - Kleiman, Norman J.; Stewart, Fiona A.; Hall, Eric J.
Highlights: Space radiation human health effects are of serious concern for long-term missions. Threats of radiological terrorism contribute to interest in radioprotective agents. Medical countermeasures to prevent or reduce radiation injury are urgently needed. Radiation cataract models are useful to test efficacy of radiation countermeasures. There is little published data on limiting HZE particle effects in eye tissue. Abstract: World events, including the threat of radiological terrorism and the fear of nuclear accidents, have highlighted an urgent need to develop medical countermeasures to prevent or reduce radiation injury. Similarly, plans for manned spaceflight to a near-Earth asteroid or journey to Mars raise serious concerns about long-term effects of space radiation on human health and the availability of suitable therapeutic interventions. At the same time, the need to protect normal tissue from the deleterious effects of radiotherapy has driven considerable research into the design of effective radioprotectors. For more than 70 years, animal models of radiation cataract have been utilized to test the short and long-term efficacy of various radiation countermeasures. While some compounds, most notably the Walter Reed (WR) class of radioprotectors, have reported limited effectiveness when given before exposure to low-LET radiation, the human toxicity of these molecules at effective doses limits their usefulness. Furthermore, while there has been considerable testing of eye responses to X- and gamma irradiation, there is limited information about using such models to limit the injurious effects of heavy ions and neutrons on eye tissue. A new class of radioprotector molecules, including the sulfhydryl compound PrC-210, are reported to be effective at much lower doses and with far less side effects. Their ability to modify ocular radiation damage has not yet been examined. The ability to non-invasively measure sensitive, radiation-induced ocular changes over long periods of time makes eye models an attractive option to test the radioprotective and radiation mitigating abilities of new novel compounds.